The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/v14122771
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Preventive Measures and Vaccination against SARS-CoV-2 on the Infection Risk, Treatment, and Hospitalization: A Cross-Sectional Study of Algeria

Abstract: Coronavirus disease (COVID-19) caused by the SARS-CoV-2 virus continues to afflict many countries around the world. The resurgence of COVID-19 cases and deaths in many countries shows a complacency in adhering to preventive guidelines. Consequently, vaccination continues to be a crucial intervention to reduce the effects of this pandemic. This study investigated the impact of preventive measures and COVID-19 vaccination on the infection, medication, and hospitalization. A cross-sectional online survey was cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 53 publications
1
15
0
Order By: Relevance
“…Despite the reduction in deaths, there is still a need to protect vulnerable groups through the achievement of high vaccination coverages and herd immunity [ 34 ]. In a cross-sectional study conducted in Algeria between 23 December 2021 and 12 March 2022, Hamimes et al [ 35 ] found that the role of preventive measures (social distancing, quarantine, and facemask wearing) was limited and insufficient for mitigating the spread of COVID-19 when people are unvaccinated; this finding highlights the importance of combining preventive measures and vaccination to control the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the reduction in deaths, there is still a need to protect vulnerable groups through the achievement of high vaccination coverages and herd immunity [ 34 ]. In a cross-sectional study conducted in Algeria between 23 December 2021 and 12 March 2022, Hamimes et al [ 35 ] found that the role of preventive measures (social distancing, quarantine, and facemask wearing) was limited and insufficient for mitigating the spread of COVID-19 when people are unvaccinated; this finding highlights the importance of combining preventive measures and vaccination to control the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, they are associated with some side effects that are mostly related to the dose used and duration of treatment. During the COVID-19 pandemic, many reported behaviors were reported regarding medications use among different countries including Middle East [36][37][38]. Furthermore, a debate on the use of corticosteroids was going on until several results of studies led to amendments recommending corticosteroids among the COVID-19 treatment guidelines in certain cases [9,39,40].…”
Section: Discussionmentioning
confidence: 99%
“…The Coronavirus disease 2019 (COVID-19) pandemic has exerted long-lasting impacts on multiple domains of health (1)(2)(3). The first COVID-19 case was identified in Wuhan, China in December 2019 (4,5).…”
Section: Introductionmentioning
confidence: 99%